PENINGKATAN KEMAMPUAN SISWA MENGANALISA MATERI KEWARGANEGARAAN MELALUI METODE VCT (VALUE CLARIFICATION TECHNIQUE) - NURHIJRAH NURHIJRAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This research is a classroom action research. The purpose of this research is to increase students' learning motivation by using the VCT method in the learning process of class XII social studies at SMA Negeri 3 Takalar and to improve students' ability to analyze civics material through the VCT method in class XII social studies at SMA Negeri 3 Takalar. The expected benefits in this study are: (1) for students to increase their learning motivation (2) for teachers to add experience and repertoire of creative and fun learning methods in the learning process. This classroom action research was conducted on students of class XII IPS I with a recycled assessment technique consisting of: (1) planning (2) action implementation, (3) observation and (4) reflection and evaluation. Data on increasing learning motivation and increasing students' ability to analyze Civics material were obtained using the instrument of observation sheets, teacher journals, questionnaire sheets and student test results twice. The data were analyzed qualitatively descriptively. The results showed that: (1) the use of the VCT method in the learning process on the basic competence of Pancasila as an open ideology can increase the learning motivation of class XII IPS I students of SMA Negeri 3 Takalar (2) the use of the VCT method in the Civics learning process on the basic competence of Pancasila as an ideology Openness can improve students' ability to analyze Civics material (3) student reflection on the use of VCT method in the learning process is generally positive (4) student learning achievement (affective and cognitive) and student life skills can be improved by using VCT in the learning process. ABSTRAKPenelitian ini merupakan penelitian tindakan kelas.. Tujuan penelitian ini untuk meningkatkan motivasi belajar siswa dengan menggunakan metode VCT dalam proses pembelajaran kelas XII IPS SMA Negeri 3 Takalar dan untuk meningkatkan kemampuan siswa menganalisis materi kewarganegaraan melalui metode VCT di kelas XII IPS SMA Negeri 3 Takalar. Manfaat yang diharapkan dalam penelitian ini adalah : (1) bagi siswa dapat meningkatkan motivasi belajarnya (2) bagi guru dapat menambah pengalaman dan khasanah metode-metode pembelajaran yang kreatif dan menyenangkan dalam proses pembelajarannya. Penelitian tindakan kelas ini dilakukan pada siswa kelas XII IPS I dengan teknik pengkajian berdaur ulang yang terdiri dari : (1) perencanaan (2) pelaksanaan tindakan (Action), (3) observasi dan (4) refleksi dan evaluasi. Data tentang peningkatan motivasi belajar dan peningkatan kemampuan siswa menganalisis materi PPKn diperoleh dengan menggunakan instrument lembar observasi, jurnal guru, lembar angket dan hasil tes ujian siswa sebanyak dua kali. Data di analisis secara kualitatif deskriptif. Hasil penelitian menunjukkan bahwa : (1) penggunaan metode VCT dalam proses pembelajaran pada kompetensi dasar Pancasila sebagai ideologi terbuka dapat meningkatkan motivasi belajar siswa kelas XII IPS I SMA Negeri 3 Takalar (2) penggunaan metode VCT dalam proses pembelajaran PPKn pada kompetensi dasar Pancasila sebagai ideologi terbuka dapat meningkatkan kemampuan siswa mengalisis materi PPKn (3) refleksi siswa terhadap penggunaan metode VCT dalam proses pembelajaran pada umumnya positif (4) prestasi belajar siswa (afektif dan kognitif) serta life skill siswa dapat ditingkatkan dengan penggunaan VCT dalam proses pembelajaran.